Patient- and endoscopist-related risk factors and etiological categorization of post-colonoscopy colorectal cancer - Lemmen, Esly; Sluiter-Post, Judith; van Stralen, Karlijn; van Soest, Ellert (Endoscopy International Open, 2025)
Colonoscopy is considered to be the gold standard for detecting colorectal cancer. However, this technique is not flawless and post-colonoscopy colorectal cancers (PCCRCs) can occur. Therefore, we investigated the association between patient- and endoscopist-related risk factors and occurrence of PCCRC.A matched case-control study design was employed. Data from the national colorectal cancer screening program, along with medical records, were used to identify patients diagnosed with colorectal cancer from 2012 until 2022 who had a negative colonoscopy in the 4 years preceding the diagnosis. Patients with colorectal cancer (cases) were matched in a 1:2 ratio with patients without colorectal cancer (controls) based on the date of the negative index colonoscopy of the cases. Analyses at the patient and endoscopist level were conducted to assess factors associated with PCCRC occurrence. Root cause analysis, using the World Endoscopy Organization categorization, was performed to identify possible PCCRC causes.Of 72,975 colonoscopies, 61 PCCRC cases (62% male, mean age 77 years) were found, resulting in an incidence of 22 per 100,000 patient years. Root cause analysis showed that over 75% of PCCRCs could be classified as a possibly missed lesion during index colonoscopy. Endoscopists with a higher mean number of adenomas per colonoscopy had significantly lower PCCRC incidence.Endoscopists detecting more adenomas had a substantially lower PCCRC incidence in their patients. Therefore, endoscopist performance is a crucial marker of PCCRC and may serve as a quality control measure for colonoscopy.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Colorectal cancer; Quality and logistical aspects; Quality management; Performance and complications; CRC screening